Regional differences of testicular artery blood flow in post pubertal and pre-pubertal dogs - de Souza, Mírley B.; Barbosa, Claudia C.; England, Gary C.W.; Mota Filho, Antonio C.; Sousa, Carmen Vládia S.; de Carvalho, Gabriela G.; Silva, Herlon Victor R.; Pinto, José N.; Linhares, Jussiara C.S.; Silva, Lúcia D.M. (BioMed Central, 2015)
Background